1997
DOI: 10.1113/jphysiol.1997.sp022027
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of the cGMP‐gated conductance of vertebrate rods block the photocurrent in scallop ciliary photoreceptors.

Abstract: 1 Hyperpolarizing scallop photoreceptors, like vertebrate rods, use cGMP as an internal messenger and their light-sensing structure is also of ciliary origin. To ascertain possible functional similarities between the light-sensitive conductances in the two classes of visual cells, we examined in scallop photoreceptors the effects of several antagonists of the photocurrent of rods. 2. Extracellular application of L-cis-diltiazem rapidly and reversibly suppressed the photocurrent. The effect was stereospecific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Although 2′4′DCB has been established as an inhibitor of Na + /Ca 2+ exchange, a closely related compound, 3′4′DCB can inhibit cyclic nucleotide–gated channels (Gomez and Nasi 1997). We were concerned that the current reductions shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although 2′4′DCB has been established as an inhibitor of Na + /Ca 2+ exchange, a closely related compound, 3′4′DCB can inhibit cyclic nucleotide–gated channels (Gomez and Nasi 1997). We were concerned that the current reductions shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the G t -mediated phototransduction of vertebrate rods and cones, it has been shown that cyclic nucleotide-gated (CNG) channels are used for generating cellular responses (4,29). Similarly, in the G o -mediated phototransduction of molluscan photoreceptors, the functioning of CNG channels for generating cellular responses was inferred from pharmacological experiments (30,31). Interestingly, we also isolated a cDNA encoding a channel, which fell into the CNG subfamily including vertebrate rod, cone, and olfactory CNGs, from the box jellyfish lens eyes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore tested another possibility, namely, that the cyclic nucleotidegated anion channel (CNG channel) participates in LTM formation. We tested two kinds of CNG channel inhibitors, l-cis diltiazem (L-DIL) and 3, 4, -dechlorobenzamil (DCB); the former has been used in many animals (Nagy 1994 in Limulus; Gotow et al 1997 in mollusks) including insects (Murata et al 2006), and the latter has been used in mollusks (Gomez and Nasi 1997). Injection of L-DIL (1 mM) or DCB (1 mM) before multiple-trial conditioning completely impaired 24-h retention, while 30-min retention was normal (Fig.…”
Section: Cyclic Nucleotide-gated Anion Channel and Calmodulin Intervementioning
confidence: 99%